Identification of multiple eigenmode growth rates in DIII-D and EAST tokamak plasmas. (9th January 2019) - Wang, Z.R.; Logan, N.C.; Munaretto, S.; Liu, Y.Q.; Sun, Y.W.; Gu, S.; Park, J.-K.; Hanson, J.M.; Hu, Q.M.; Strait, T.; Nazikian, R.; Kolemen, E.; et al.
Abstract: The successful application of three-dimensional (3D) magnetohydrodynamic (MHD) spectroscopy in the stable DIII-D and EAST plasmas enables to directly extract the multi-mode plasma transfer function in tokamak experiments. The transfer function not only reveals the contribution of each dominant MHD eigenmode in the multi-model plasma response, but also quantifies the corresponding eigenvalue which is the critical stability index of MHD mode. The method performs the active detection of stable plasma by utilizing the upper and lower rows of internal coils to scan the frequency and poloidal spectrum of the applied 3D field, and reconstructing the multi-mode transfer functions model through the least square fitting of the plasma response measured by 3D-field magnetic sensors distributed at different poloidal locations. The results point to the potential development of an advanced strategy for tracking the plasma stability based on the extracted eigenvalues of stable modes. The improved understanding of the dominant eigenmodes' behavior in multi-mode plasma response through transfer function can also help to optimize the applied 3D fields for the purposes, such as the type-I edge localized mode suppression and the core stability control in future fusion reactors.